MODEL TERINTEGRASI DARI KESETIAAN PELANGGAN PADA BANK PEMERINTAH - Yunita Nila Dewi (Jurnal Manajemen dan Pemasaran Jasa, 2014)
This study aimed to analyze the influences of service quality and image on customer loyalty from customer satisfaction that useful for marketing managers in making decisions for the company.This study was conducted on the state banks customers and took 200 customers becamesamples. This study used Structural Equation Model (SEM). The method used is a non probability sampling with purposive sampling techniques. Based on the results of this study is that there’s positive influence of service quality on customer satisfaction and influence of image on customer satisfaction. Furthermore, the customer satisfaction positive influence on customer loyalty, but there’s no positive influence of service quality on customer loyalty from customer satisfaction. Furthermore there’s no positive influence of image on customer loyalty from customer satisfaction.Keywords : Service Quality, Image, Customer Satisfaction, Customer Loyalty